2010
DOI: 10.1007/s00453-010-9461-6
|View full text |Cite
|
Sign up to set email alerts
|

Shortest Paths in Time-Dependent FIFO Networks

Abstract: In this paper, we study the time-dependent shortest paths problem for two types of time-dependent FIFO networks. First, we consider networks where the availability of links, given by a set of disjoint time intervals for each link, changes over time. Here, each interval is assigned a non-negative real value which represents the travel time on the link during the corresponding interval. The resulting shortest path problem is the time-dependent shortest path problem for availability intervals (T DSP int ), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Such queries can be dealt with by range searches, which compute the travel time function between two points. There exist Dijkstra-based algorithms [71] for this problem, and most speedup techniques can be adapted to deal with this as well [32,72].…”
Section: Time-dependencementioning
confidence: 99%
“…Such queries can be dealt with by range searches, which compute the travel time function between two points. There exist Dijkstra-based algorithms [71] for this problem, and most speedup techniques can be adapted to deal with this as well [32,72].…”
Section: Time-dependencementioning
confidence: 99%
“…In [48], it has been shown that within the same time complexity, for a given start time at s, not only the minimum travel time to d can be computed, but it is also possible to obtain the slope of the function at that time. This can be used in Algorithm Aprx-B as a heuristic improvement to reduce the number of computations by using the function tangent rather than lines connecting consecutive sample points.…”
Section: Discussionmentioning
confidence: 99%
“…We study two variants of the problem [47,48]. First, we consider networks in which the availability of links, changes over time.…”
Section: Problemsmentioning
confidence: 99%
See 2 more Smart Citations